Luka płacowa oparta na płci w przypadku kobiety na stanowiskach kierowniczych. Kraje Grupy Wyszechradzkiej w świetle sytuacji w Unii Europejskiej - Kłysik-Uryszek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2020)
This research investigates the level of the gender pay gap and gender parity in the Visegrad Group countries in light of the changes that took place in the whole EU during the last decade. The following hypotheses accompany the research objective: (1) the level of the gender pay gap diminished significantly over the last decade in the V4 economies; (2) the V4 countries are following a path to achieve gender parity. Data were taken from Eurostat. The pay gap and the managerial occupations indicators were used to verify the research hypotheses. The empirical investigation did not let us reject the first hypothesis for Poland only. However, it should be rejected for the other V4 economies. In addition, the second hypothesis should be rejected.